Application of PGPR and Antagonist Fungi-based Biofungicide for White Rust Disease Control and Its Economyc Analysis in Chrysanthemum Production - Hanudin Hanudin; Kurniawan Budiarto; Budi Marwoto (AGRIVITA, Journal of Agricultural Science, 2017)
Plant growth promoting rhizobacteria (PGPR) application in combination with other antagonist microbes as biopesticide have been considered in many crops. Our research was conducted to evaluate the efficacy of these useful combinations with the carrying agent for growth promotion, thus lowering white rust incidence in chrysanthemum production. The experiment was carried out at three cooperative farmer sites located in Cipanas, Cianjur, West Java, Indonesia from January to December 2016. The production process was arranged in a paired treatment; a combination of PGPR and antagonist fungi (without supplemental chemical fertilizers and fungicide), furtherly called biofungicide and common farmer practices. The results showed that the application of biofungicide promoted equal plant growth quality as common practices. White rust incidency was lower at biofungicide treatment sites, thus increased the markertable flowers quantity. The production cost was considered more efficient in biofungicide sites, due to cheaper price of biofungicide than chemical fertilizers and fungicide. The increase of marketable stalks and cost efficiency led to an increase of net income of biofungicide-based production as also viewed from higher Revenue Cost Ratio (R/C) than common farmer practices.